Gene Therapy for Systemic or Organ Specific Delivery of Manganese Superoxide Dismutase - Joel S. Greenberger; Amitava Mukherjee; Michael W. Epperly (MDPI AG, 2021)
Manganese superoxide dismutase (MnSOD) is a dominant component of the antioxidant defense system in mammalian cells. Since ionizing irradiation induces profound oxidative stress, it was logical to test the effect of overexpression of MnSOD on radioresistance. This task was accomplished by introduction of a transgene for MnSOD into cells in vitro and into organs in vivo, and both paradigms showed clear radioresistance following overexpression. During the course of development and clinical application of using MnSOD as a radioprotector, several prominent observations were made by Larry Oberley, Joel Greenberger, and Michael Epperly which include (1) mitochondrial localization of either manganese superoxide dismutase or copper/zinc SOD was required to provide optimal radiation protection; (2) the time required for optimal expression was 12-18 h, and while acceptable for radiation protection, the time delay was impractical for radiation mitigation; (3) significant increases in intracellular elevation of MnSOD activity were required for effective radioprotection. Lessons learned during the development of MnSOD gene therapy have provided a strategy for delivery of small molecule SOD mimics, which are faster acting and have shown the potential for both radiation protection and mitigation. The purpose of this review is to summarize the current status of using MnSOD-PL and SOD mimetics as radioprotectors and radiomitigators.